Draft Annual Plan Tamil Nadu 2011-2012 - Planning Commission (Planning Commission, 2011)
The Eleventh Five Year Plan (2007-12) was formulated with the broad objectives of ensuring steady and sustainable economic growth coupled with social justice, safeguard the livelihoods of people, and to improve the quality of life of the urban and rural population. Accordingly, the Annual Plans from 2007-08 to 2010-11 were evolved within the Five Year Plan framework.
Government of Tamil Nadu, State Planning Commission